Ethnobotanic features of plants used by inhabitants in Bozova (Şanliurfa-Turkiye) - Kaya, Ömer Faruk; Oymak, Emine; Tosyagulu Celik, Hatice (Ethnobotany Research and Applications, 2025)
Background: This study aims to determine the intended purpose underlying the usage of plants by the inhabitants of Bozova (Şanlıurfa), and to demonstrate significance of such plants regarding ethnobotanical features. Methods: Reference person research, survey study and field studies for picking up the plants during certain vegetation periods were carried out. Results: 133 general and 171 taxa (2 genera, 110 species, 38 subspecies, 21 varieties) belonging to 50 families were identified as result of the research on the field. 1 of the plants belongs to Fungi kingdom, Ascomycota divisio; the others belong to Plantae kingdom, Spermatophyta divisio, Gymnospermae (1 taxon) and Angiospermae (169 taxa) subdivisio. By number of taxa they contain, top families in the area were Fabaceae (31), Asteraceae (24), Lamiaceae (14), Apiaceae (10), Brassicaceae (10), and Poaceae (6). By number of species they contain, top species in the area were Trifolium (9), Trigonella (6), Convolvulus (4), Astragalus (3), Centaurea (3), Euphorbia (3) and Medicago (3). The taxa identified in the research area wereused for different purposes, for example; 61 for food, 48 for medical purpose, 35 as fodder, 9 for roofage, 8 as household goods, 7 for spice/flavoring, 5 for games, 5 for fuel, 5 for ornament, 4 as amulet/incense, handicraft (natural painting, broom, woodwork), 3 for fragrance, 2 for against evil eye, 2 for painting, and it is further observed that other taxa wereused for different purposes. Besides, 10 of these plants wereidentified as harmful, while 8 plants wereknown only by their names. Also, other ethnobotanical studies conducted in the surrounding neighbourhood of the study area were compared by using Jaccard Index. Conclusions: New use methods of the plants determined in our study were revealed. We applied FIC to determine that all villagers use plants for the same purposes and informing each other, and as a result, we found that everyone in the study area uses the same taxa for the same disease groups with similar usage methods. Keywords: ethnobotany, vernacular name, Jaccard Index, FIC, Bozova, Şanlıurfa, Türkiye